2002
DOI: 10.1071/ea01063
|View full text |Cite
|
Sign up to set email alerts
|

Cotton pollination by honeybees

Abstract: In a field trial, significant increases for the total number of bolls harvested (11.1%), total mass of bolls (16.5%), total lint mass (15.8%), total seed mass (19.7%) and total number of seeds per sample (16.5%) were obtained from plots receiving the highest number of bee visits compared with plots receiving the lowest number of bee visits. Lint-quality examinations resulted in a significant improvement for micronaire and fineness with increased bee visits. Non-significant increases were obtained for the mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Determinate or indeterminate flowering patterns likely play a role in attractiveness. For example, a single cotton flower opens at dawn, withers in the afternoon, closes by sunset and never reblooms, thereby providing only morning nectar resources for bees . The interplay of these variables also affects how bees use a crop.…”
Section: Crop‐ and Bee‐specific Variables Related To Attractivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinate or indeterminate flowering patterns likely play a role in attractiveness. For example, a single cotton flower opens at dawn, withers in the afternoon, closes by sunset and never reblooms, thereby providing only morning nectar resources for bees . The interplay of these variables also affects how bees use a crop.…”
Section: Crop‐ and Bee‐specific Variables Related To Attractivenessmentioning
confidence: 99%
“…For example, a single cotton flower opens at dawn, withers in the afternoon, closes by sunset and never reblooms, thereby providing only morning nectar resources for bees. 20 The interplay of these variables also affects how bees use a crop. For instance, crops with relatively low attractiveness may still be, at certain times, an important source of food for bees.…”
Section: Seasonal and Daily Availabilitymentioning
confidence: 99%
“…This implies that plants close to the city flowered earlier than those outside of the city. Moreover, even though cotton can self-pollinate, more cotton is obtained when pollinators are present (Rhodes, 2002). The advancement in cotton planting may have implications for pollination by insects-especially bees-if the pollinating insects are not (as) available when the plants are blooming.…”
Section: Economic Ramificationsmentioning
confidence: 99%
“…Photo credit: K. E. LeVan. Moreover, bee pollination (Waller et al 1985), especially by honey bees (Rhodes 2002) and bumble bees (Berger et al 1988, Van Deynze et al 2005, can enhance reproduction in cotton up to 38% (Delaplane and Mayer 2000). Previous work has demonstrated that interactions between the cotton aphid and the imported red fire ant (Solenopsis invicta) increase cotton reproduction because fire ants consume nonaphid herbivores that are more damaging to cotton compared to aphids (Styrsky and Eubanks 2010).…”
Section: Introductionmentioning
confidence: 99%